Regulation of RNA Interference Pathways in the Insect Vector Laodelphax striatellus by Viral Proteins of Rice Stripe Virus - Yan Xiao; Qiong Li; Wei Wang; Yumei Fu; Feng Cui (Viruses, 2021)
RNA interference (RNAi), especially the small interfering RNA (siRNA) and microRNA (miRNA) pathways, plays an important role in defending against viruses in plants and insects. However, how insect-transmitted phytoviruses regulate the RNAi-mediated antiviral response in vector insects has barely been uncovered. In this study, we explored the interaction between rice stripe virus (RSV) and the miRNA and siRNA pathways of the small brown planthopper, which is a vector insect. The transcript and protein levels of key genes in the two RNAi pathways did not change during the RSV infection process. When the expression of insect Ago1, Ago2, or Translin was silenced by the injection of double-stranded RNAs targeting these genes, viral replication was promoted with Ago2 silencing but inhibited with Translin silencing. Protein-protein binding assays showed that viral NS2 and RNA-dependent RNA polymerase interacted with insect Ago2 and Translin, respectively. When NS2 was knocked down, the transcript level of Ago2 increased and viral replication was inhibited. Therefore, viral NS2 behaved like an siRNA suppressor in vector insects. This protein-binding regulation of insect RNAi systems reflects a complicated and diverse coevolution of viruses with their vector insects.